Pengaruh Media Video Berbahasa Arab Terhadap Keterampilan Mendengar dalam Pembelajaran Bahasa Arab - Khairy Abusyairy; Ahmad Fadhel Syakir Hidayat; Nur Syakinah (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
The effect of a video using the Arabic speaker on the listening skill in teaching the Arabic language for eighth grade students at the one governmental secondary school in Kababan. Research, Department of Arabic Language Education in the College of Education and Teacher Education, Sultan Aji Muhammad Idris State Islamic University, Samaranda. This research is under the supervision of Mr. Khairy Abu Siry, master's degree as the first supervisor, and Mr. Ahmed Fadel Shaker Hedayat, master's degree, as the second supervisor. In teaching Arabic, listening skill is a very important aspect in addition to the first skill that aims to understand the meaning of what is heard. In teaching Arabic, the originality of the language is essential for the listeners. Thus, to develop this skill, a natiq (Arabic speaker) is needed in a natural form. The type of research used is quantitative research. The method used is an experimental method with an unequal control group design. The data tools used in this research were test, interview and documentation. The research community is all eighth-grade students in one public secondary school in Kababan, with the sample eighth-grade students -1 as the control group and eighth-grade students -4 as the experimental group using the sampling technique in the form of non-probability sampling, that is, purposive sampling. Based on the results of data analysis using SPSS, it can be seen that Asymp.Sig 2-tailed is 0.000. Because the value of 0.000 is less than 0.05, Ho is rejected and Ha is accepted. That is, there is an average difference between the results of education before and after the test, so that it can be said that there is an effect of using the video medium with the Arabic speaker in teaching the Arabic language among the eighth grade students in the one governmental secondary school in Kababan by 23.5%.